Does tax education conducted by the Inland Revenue Board Malaysia lead to better tax compliance amongst individual taxpayers in the Petaling Jaya branch? / Norzilah Hassan - Hassan, Norzilah (2014)
Tax education has always been one of central focus to Inland Revenue Board Malaysia. It reflects the commitment of the agency to educate taxpayer in every possible ways. The objective of this study is to determine whether tax education program tax been implemented in Petaling Jaya Branch does effect the compliance among the tax payer. The sample was randomly selected from population by using random sampling technique and was distributed with 60 responses as a sample of this research at Petaling Jaya Branch. The data collected were analyzed by using descriptive statistic. The questionnaire were given during talks that conducted by officer in Petaling Jaya Branch. A number of previous literatures are cited with view to determine relationship between tax education and tax compliance. With the availability of secondary data gain from the Annual Report of Inland Revenue Board Malaysia we can see the effect of tax education does increase tax compliance generally.Based on the findings, Petaling Jaya’s Taxpayers really used the information on tax education wise. Beside still need some improvement, it still the best practise to encourage more people to know and learn about tax. It shows that Petaling Jaya’s taxpayers have a good perception toward tax education programmed. For the future research, this study suggested boosting the positive perception toward tax education programmed of the tax payer to give the tax payers more exposure on tax education programmed